Nuzulul qur’an : turunnya al-qur’an dan implementasinya dalam pendidikan - Jadidah, Nur (Maliki Interdisciplinary Journal, 2025)
The Quran was revealed gradually over about 23 years to the Arab society at that time. The Quran comments on the situations and events they experienced and provides answers to questions and problems they encountered. Many answers in the Quran are direct rebuttals to the social norms prevailing in the Jahiliyyah society. The content of the Quran not only transformed the existing social structure but also revolutionized existing concepts, replacing them with new ideas that are clearer and liberating. The Quran was revealed gradually. This procedure allowed Muslims to gradually avoid many Jahiliyya customs by understanding the development of laws within the Quran and slowly implementing regulations to address various social issues. This method had a significant impact on the work of da’wah and lessened the burden on the Prophet when receiving revelations. The gradual revelation of the Qur’an has the potential to elevate the educational standards of Muslims by transforming behavior, healing minds, shaping character, and enhancing lives. The slow progression of the Qur’an into the realm of education and teaching has benefits in promoting the creation of instructional systems and facilitating memorization, understanding, and conveying of teachings. The aim of this study is to help us gain a comprehensive understanding of the importance of the advent of Islam and empower us to make better choices regarding our current social situation by utilizing Qur’anic revelation for the lives of Muslims.